In vitro fermentation of yeast cell walls (mannan-oligosaccharide) and purified β-glucans modulates the colonic microbiota of dogs with inflammatory bowel disease and demonstrates protective effects on barrier integrity and anti-inflammatory properties - Jonas Ghyselinck; Lynn Verstrepen; Maike Rakebrandt; Sofie Marynissen; Sylvie Daminet; Massimo Marzorati (PLoS ONE, 2025)
Inflammatory bowel disease (IBD) is characterized by a disruption of intestinal homeostasis, chronic inflammation, and dysbiosis. Prebiotic supplementation may be useful for managing IBD in dogs. The aim of the study is to investigate the effects of two prebiotics, Biolex MB40 or Leiber Beta-S, on the gut microbiota isolated from three dogs with IBD, using the Colon-on-a-plate technology. Biolex MB40 and Leiber Beta-S contain concentrated 1,3–1,6- β-D-glucan isolated from the Saccharomyces cerevisiae cell walls. Biolex MB40 also contains mannan-oligosaccharide (MOS). Wells of the Colon-on-a-plate set up were inoculated with fecal suspensions and supplemented with either Biolex MB40 and Leiber Beta-S, or no test product (blank). Following 48h incubation, bacterial metabolites were measured and 16S rRNA targeted gene sequencing was performed. Colonic supernatants were added to a Caco-2/THP1 co-culture model to evaluate their effects on barrier integrity upon inflammation-induced barrier disruption and interleukin (IL)-10 production. Acetate and propionate concentrations were significantly increased versus blank with Biolex MB40, and biologically relevant numerical increases were observed with Leiber Beta-S supplementation. A donor-dependent, biologically relevant increase in butyrate was observed with both test products versus blank. Alpha diversity and microbiota biomass were increased, as well as the abundance of the five predominant phyla with both test products relative to blank. The greatest increases in abundance were observed for the Bacteroidetes and Firmicutes phyla. Fermentation of both test products had a protective effect on the gut epithelial barrier (measured by transepithelial electrical resistance) that was donor dependent. IL-10 production was significantly increased with Biolex MB40 supplementation for all donors, and with Leiber Beta-S supplementation for one donor. These in vitro findings confirm a prebiotic effect for both products and suggest that supplementation with either Biolex MB40 or Leiber Beta-S may have beneficial effects on the gut microbiota of dogs with IBD.